Analisis Keterbukaan Informasi Publik Terhadap Partisipasi Masyarakat dalam Pembangunan Desa (Kecamatan Kedungwuni Kabupaten Pekalongan) - Mafturrahman, Mafturrahman; Elshifa, Aria; Anjarini, Ary Dwi (LPPM Institut Pendidikan Nusantara Global, 2024)
Openness of public information, community participation and village development are the expectations of everyone, as well as the village community of Kedungwuni Sub-district, Pekalongan Regency. However, everything must be supported by adequate human resources and be able to understand their rights and obligations based on the applicable laws and regulations. The purpose of this research is to analyze and explain the importance of public information disclosure and community participation in village development. This research method uses a qualitative method with descriptive analysis. To analyze and explain the existence of public information disclosure, community participation in village development in Kedungwuni District, Pekalongan Regency. The results of this study, namely: The village government in opening public information has been carried out with the existence of village information boards and village websites. However, community participation is still quite low, so it does not significantly affect village development. Based on the findings of this study, the authorities should make the best innovations so that the village community has the awareness to participate in village development activities.